Altering the Composition of Caseicins A and B as a Means of Determining the Contribution of Specific Residues to Antimicrobial Activity - Norberg, Sarah (American Society for Microbiology (ASM), 2011)
Caseicin A (IKHQGLPQE) and caseicin B (VLNENLLR) are antimicrobial peptides generated through the bacterial fermentation of sodium caseinate, and on the basis of this and previous studies, they are active against many Gram-negative pathogens (Cronobacter sakazakii, Cronobacter muytjensii, Salmonella enterica serovar Typhimurium, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas fluorescens) as well as the Gram-positive organism Staphylococcus aureus. Here we describe further studies with the aim of establishing the importance of specific (charged and nonpolar aliphatic) residues within the caseicin peptides and the effects that they have on the bacteria listed above. In order to achieve our objective, we created four derivatives of each caseicin (A1 to A4 and B1 to B4) in which specific residues were altered, and results obtained with these derivatives were compared to wild-type caseicin activity. Although conversion of cationic residues to alanine in caseicins B1 (R8A change), A1 (K2A), A2 (H3A), and A3 (K2A-H3A) generally resulted in their activity against microbial targets being reduced or unaltered, C. sakazakii DPC6440 was unusual in that it displayed enhanced sensitivity to three peptides (caseicins A1, A3, and B2) in which positively charged residues had been eliminated. While the replacement of leucine with alanine in selected variants (B3 and B4) resulted in reduced activity against a number of strains of Cronobacter and, in some cases, S. Typhimurium, these changes enhanced the activities of these peptides against DPC6440 and a number of S. aureus strains. It is thus apparent that the importance of specific residues within the caseicin peptides is dependent on the strain being targeted.